Geochemistry of some Ferrar Large Igneous Province intrusive rocks in the Transantarctic Mountains, Antarctica - Harris, Megan C. (The Ohio State University, 2014)
The Ferrar Large Igneous Province is a widespread magmatic event associated with the break-up of Gondwana during the Jurassic Period. The Ferrar outcrops over a distance of 3000 km throughout the Transantarctic Mountains. It consists of the Ferrar Dolerites, the Dufek intrusion, Kirkpatrick basalts and pyroclastic rocks. Twenty samples collected from Ferrar sills within the Beardmore Glacier region and elsewhere were analyzed to determine the presence of additional olivine-bearing sills and the continuity of the Mount Fazio Chemical Type (MFCT) composition throughout the region. All samples analyzed have been determined to be of the MFCT composition, including a set of samples that are olivine-bearing, and a single sample that belongs to the Dufek intrusion rather than the Ferrar Dolerite. The research expands the geochemical data base and stratigraphic coverage of the Ferrar Large Igneous Province. Arts and Sciences Undergraduate Research Scholarship Shell Exploration and Production Company NSF Grant ANT 0739720 A five-year embargo was granted for this item.